Managing Knowledge and Overcoming Resistance to Change: A Case Study at Firat University - Varol, Nurhayat; Varol, Serkan (Acad Conferences Ltd, 2013)
The purpose of this paper is to examine the relationship between knowledge and overcoming resistance to change in class projects at Firat University in Turkey. Resistance to change among departments is a major issue for individuals at organizations. It may cause stress and frustration at work environments. Even, the change can extend to layoffs which eventually destroy the overall work atmosphere within departments. Employees often set in their ways, and don't want to modify their routine. However, organizations need to change to continue delivering the right products and services on time and effectively due to emerging demands in industry. The major reason behind resistance to change is strongly correlated to knowledge management aspects. The lack of individual's knowledge in another field may fear him or her losing the job if an interchange occurs among departments. Because the employee is assigned to adopt a designated duty, it is unlikely to appoint the individual in another field that he or she is unfamiliar with. Thus, the learning curve for an existing experienced operator is much longer than a new employee. Besides organizations, the assignment changes in classroom project tasks may also create similar atmosphere among students. However, the causes of this hypothesis are firmly depending upon managing motivation and knowledge factors. Therefore, in this research, a matrix chart will be presented that evaluates students' performances at different in class projects at Firat University, which interprets how managing knowledge leverages the issues of resistance to change in order to increase productivity and decrease potential conflicts among students.
10th International Conference on Intellectual Capital, Knowledge Management and Organisational Learning (ICICKM) -- OCT 24-25, 2013 -- George Washington Univ, Washington, DC
Keywords: learning curve; managing knowledge; motivation; organization; resistance to change